The effect of EKORMIN on rats with diabetes mellitus model: effectiveness on fasting blood glucose, MDA, and insulin levels - Siti Nurjana Kurniaty Tanaiyo; Budiyanti Wiboworini; Setyo Sri Rahardjo (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Antioxidant use for additional diabetes mellitus therapy is growing, such as okra (Abelmoschus esculentus) and turmeric (Curcuma longa), which are rich in flavonoids and have beneficial effects on diabetes mellitus. This study aimed to determine the effects of okra turmeric extract (EKORMIN) on Fasting Blood Glucose (FBG), malondialdehyde (MDA), and insulin levels in diabetic rats. The research was conducted from December to January 2022 at PSPG UGM using experimental research with a pre-posttest-controlled group design. White male Wistar rats (n = 35) randomly grouped into five: negative control (STZ-NA), positive control (STZ-NA+metformin 1,8 mg/200 gBW), P1 (STZ-NA+EKORMIN low dose 130,5;110,5 mg/kgBW), P2 (STZ-NA+EKORMIN moderate dose 261;221 mg/kgBW), P3 (STZ-NA+EKORMIN high dose 522;442 mg/kgBW). The intervention lasted 14 days. Data analysis was performed using one-way analysis of variance statistical tests and post hoc follow-up tests. EKORMIN in all doses, EKORMIN reduced FBG and MDA levels and increased insulin levels (p<0,05). P2 and P3 were not significantly different from the metformin (PG) group (p>0,05). The decrease in FBG (-167,05±-2,8 vs -175,86±-1,4 mg/dL) and MDA levels (-6,32±0,33 vs -7,98±0,07 nmol/ml) P3 was higher than P2. Similarly for increased insulin levels (121,47±3,03 and 164,09±4,48 pg/ml). EKORMIN was effective in reducing FBG and MDA levels and increased insulin levels in diabetic rats. EKORMIN has antidiabetic effects and has potential for type 2 diabetes mellitus treatment.